Manuscripts With The Seals Of Kokand Khan Sayid Muhammad Khudayar Khan - Abdullaev Ravshanjon (Researchparks Publishing, 2023)
In this article, the seals of Khudayar Khan and the manuscripts with these seals will be discussed. Views regarding the preservation of these manuscripts of the palace and other institutions are also stated.